Nitrogen optimization on rhamnolipid biosurfactant production from Pseudoxanthomonas sp. G3 and its preservation techniques - Purwasena, Isty Adhitya; Astuti, Dea Indriani; Utami, Salsabila Ghina (Penerbit Universiti Kebangsaan Malaysia, 2020)
Biosurfactant is a microbial bioproduct that is used to reduce the surface tension, and can acted as emulsifier, dispersant, and anti-adhesive. Optimization of biosurfactant production needs to be done, not only to increase its production quantity, but also to reduce overall production cost. This study aims to determine the most suitable and optimum concentration of nitrogen source for biosurfactant production and its preservation techniques. The biosurfactant was produced by Pseudoxanthomonas sp. G3 using minimal salt medium with 2% light crude oil as carbon source and different nitrogen sources in the form of urea, sodium nitrate, and ammonium nitrate. The activity of biosurfactants were measured by emulsification index (E24), interfacial tense (IFT), oil drop assay, and dry weight. Potassium sorbate 0.2% (w/v) was used as preservative agent. The results showed that biosurfactant production using sodium nitrate as a nitrogen source provides the highest activity and yield. The E24 value was 76.63% and the clear zone diameter observed was 0.875 cm. The overall decreased in IFT was 35.4% and the biosurfactant dry weight was 0.45 gL-1. Microbial contamination occurred after 3 weeks of storage in the treatment without the addition of preservative. It also showed that the activity of biosurfactants (emulsification and IFT) were gradually decreased during storage. In conclusion, the optimum biosurfactant production by Pseudoxanthomonas sp. G3 was obtained by the addition of sodium nitrate 0.3% (w/v). Meanwhile, the most effective biosurfactant preservation method was by adding potassium sorbate which was stored at 4 ℃.